Slope Stability Analysis on Railroad Line in Lahat Lubuk Linggau, South Sumatra - Rika Nuraini; Abul Fida Ismaili (University of Technology Yogyakarta, 2022)
The Lahat Lubuklinggau railroad line is a strategic railroad line in the DIVRE III area of South Sumatra. Several incidents have occurred there in recent years. The incidents indicate the condition of the railroad at Lahat Lubuklinggau crossing is prone to landslides and subsidence areas, which can disrupt rail traffic. Consequently, it results in the inconvenience of train travel, which threatens the safety of rail traffic if not immediately get comprehensive repair. This study aims to analyze the vulnerability of slopes in the Lahat-Lubuklinggau railroad area using the GEO5 program to determine the slope safety number, which shows the stability of the slopes. GEO5 programs are designed to perform deformation and stability analysis in geotechnical engineering. The analytical methods used include Bishop, Fellenius, Spencer, and Janbu. After modeling and analyzing slopes using the GEO5 program, the soil reinforcement increased the safety factors according to SNI 8460:2017. With the use of slope reinforcement, the increased value of the safety factor supports the operation of train travel in the Lahat Lubuklinggau South Sumatra.